The Art of Provisionalism - Carter, Robin (East Carolina University, 2020)
Art is in itself meaningless; the significant thing to consider is the social formation and how it is reproduced. If an artwork is assigned a value, it is due to the iterative ability of the subjects involved. The most efficient means of artistic production is then the one that anticipates the interpellative function of its subjects, the inadequacy of the artistic medium, and the political climate of the moment. As such, the production of this work is contingent upon the eternal deferral of aesthetic signification and the temporal window(s) of application. This document serves as an attempt to engage with these terms and to formulate a theory for the art of Provisionalism.
Keywords: Art and society; Thoughtfulness--Art; Art--Political aspects